NK cell and Th17 responses are differentially induced in murine cytomegalovirus infected renal allografts and vary according to recipient virus dose and strain. Issue 11 (7th May 2018) - Li, Mao; Boddeda, Srinivasa Rao; Chen, Bo; Zeng, Qiang; Schoeb, Trenton R.; Velazquez, Victoria M.; Shimamura, Masako
Abstract : Human cytomegalovirus (HCMV) donor positive (D+) serostatus with acute rejection is associated with renal allograft loss, but the impact of recipient positive (R+) serostatus is unclear. In an allogeneic renal transplant model, antiviral natural killer (NK) and CD8+ T cell memory responses in murine CMV (MCMV) D+/R+ transplants were compared to D‐/R‐ and D+/R‐ transplants, with recipient infection varied by MCMV dose and strain. D+/R‐ transplants had high primary antiviral cytolytic (interferon‐γ+) and cytotoxic (granzyme B+) NK responses, whereas NK memory responses were lower in D+/R+ recipients receiving a high primary MCMV dose. Despite MCMV immunity, D+/R+ recipients receiving a low MCMV dose showed primary‐like high cytolytic and cytotoxic NK responses. D+/R+ transplants infected with different D/R strains had low cytolytic NK responses but high cytotoxic NK responses. NK memory also induced a novel TNF‐α+ NK response among high‐dose virus recipients. MCMV+ transplants had greater Th17 responses than MCMV‐uninfected transplants and Th17 inhibition ameliorated graft injury. All MCMV+ recipients had similar CD8+ T cell responses. In sum, NK and Th17 responses, but not CD8+ T cells, varied according to conditions of primary recipient infection. This variability could contribute to variable graft outcomes in HCMV D+/R+ renal transplantation. Abstract : Among murine cytomegalovirus (CMV) D+/R+ renal transplants, recipient cytolytic and cytotoxic natural killer (NK) cell and Th17 responses are associated with histologic damage and vary with recipient virus dose and strain, suggesting that NK and Th17 recipient responses contribute to CMV‐associated renal allograft injury.